2013
DOI: 10.1161/atvbaha.112.300275
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Amide Hydrolase Deficiency Enhances Intraplaque Neutrophil Recruitment in Atherosclerotic Mice

Abstract: Objective-Endocannabinoid levels are elevated in human and mouse atherosclerosis, but their causal role is not well understood. Therefore, we studied the involvement of fatty acid amide hydrolase (FAAH) deficiency, the major enzyme responsible for endocannabinoid anandamide degradation, in atherosclerotic plaque vulnerability. Methods and Results-We assessed atherosclerosis in apolipoprotein E-deficient (ApoE -/-) and ApoE -/-FAAH -/-mice. Before and after 5, 10, and 15 weeks on high-cholesterol diet, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…The indirect and sustained activation of CB1 needs to be carefully addressed in the context of the cardiovascular system, since genetic deletion of FAAH in a doxorubicin-induced cardiomyopathy model promotes myocardial injury (600). Moreover, chronic pharmacological FAAH inhibition enhances intraplaque neutrophil recruitment in atherosclerotic mice (467).…”
Section: Cardiovascular System: Blood Pressure Cardiometabolic Riskmentioning
confidence: 99%
“…The indirect and sustained activation of CB1 needs to be carefully addressed in the context of the cardiovascular system, since genetic deletion of FAAH in a doxorubicin-induced cardiomyopathy model promotes myocardial injury (600). Moreover, chronic pharmacological FAAH inhibition enhances intraplaque neutrophil recruitment in atherosclerotic mice (467).…”
Section: Cardiovascular System: Blood Pressure Cardiometabolic Riskmentioning
confidence: 99%
“…These mice have strongly increased anandamide levels, in particular in brain and liver, confi rming the key role of FAAH in anandamide degradation ( 11,18 ). We recently demonstrated that FAAH defi ciency in atherosclerosis-prone mice leads to the development of an unstable atherosclerotic plaque phenotype due to enhanced neutrophil recruitment ( 19 ).…”
Section: Histological and Morphometric Analysismentioning
confidence: 81%
“…Our latest published fi ndings demonstrate that FAAH defi ciency leads to a striking increase of neutrophil recruitment into atherosclerotic plaques ( 19 ). This was related to enhanced expression of pro-infl ammatory Th1 cytokines (TNF-␣ , IFN-␥ ) and increased local expression of neutrophil chemoattractant CXCL1 in mice lacking FAAH.…”
Section: Therapeutic Benefi T Of Cb 1 Antagonism On Neointima Formatimentioning
confidence: 84%
See 2 more Smart Citations